1980
DOI: 10.1152/ajpendo.1980.239.3.e169
|View full text |Cite
|
Sign up to set email alerts
|

Site of enhanced insulin sensitivity in exercise-trained rats at rest

Abstract: Spontaneously exercised rats show at rest enhanced responsiveness to exogenous insulin and lower plasma insulin levels after oral glucose than sedentary control rats. To assess insulin sensitivity of specific organs, glucose uptake by perfused hindlimb muscle and liver from resting exercise-trained rats was compared with perfused organs from control rats. Glucose uptake, assessed by metabolic clearance formulas, was 17% faster in hindlimbs from exercise-trained rats when perfused without added insulin and 43% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
99
2
3

Year Published

1983
1983
2002
2002

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 25 publications
5
99
2
3
Order By: Relevance
“…5 ' 6 Sprague-Dawley rats become insulin resistant, hyperinsulinemic, and hypertrigryceridemic when fed a fructose-enriched diet, 7 - 8 and the fact that this dietary manipulation also leads to an increase in blood pressure 8 lends further support to the possibility that insulin resistance and hyperinsulinemia may play a role in the genesis of high blood pressure. Furthermore, we have shown that exercise training of rats, which enhances insulin sensitivity 9 and reduces fructose-induced hyperinsulinemia, 10 also attenuates the increase in blood pressure seen in fructose-fed rats.…”
Section: W E Have Recently Speculated That Resistancementioning
confidence: 85%
“…5 ' 6 Sprague-Dawley rats become insulin resistant, hyperinsulinemic, and hypertrigryceridemic when fed a fructose-enriched diet, 7 - 8 and the fact that this dietary manipulation also leads to an increase in blood pressure 8 lends further support to the possibility that insulin resistance and hyperinsulinemia may play a role in the genesis of high blood pressure. Furthermore, we have shown that exercise training of rats, which enhances insulin sensitivity 9 and reduces fructose-induced hyperinsulinemia, 10 also attenuates the increase in blood pressure seen in fructose-fed rats.…”
Section: W E Have Recently Speculated That Resistancementioning
confidence: 85%
“…21 -23 On the other hand, exercise training in rats has repeatedly been reported to be associated with an enhanced insulin sensitivity. 24,25 We recently reported that exercise training in OVX rats results in an improvement of the insulin-resistant condition without any reduction in body weight. 7 From the present data, it may be suggested that a reduction in body fat contributes to the exercise training-induced improvement in insulin sensitivity in OVX rats.…”
Section: Body Composition In Ovariectomized Trained Ratsmentioning
confidence: 99%
“…4 - 7 Based on these findings, we raised the possibility that the changes in insulin action and concentration noted in fructose-fed rats with hypertension may play a role in the pathogenesis of the elevated blood pressure seen in this situation. In this context, we have previously demonstrated that insulin-stimulated glucose uptake is enhanced in exercise-trained rats 8 and that the hyperinsulinemia associated with feeding rats a high fructose diet is 130 HYPERTENSION VOL 12, No 2, AUGUST 1988 were placed individually in exercise wheel cages (Wahman, Timonium, MD, USA) and allowed to run at their own pace. The cages, as supplied by the manufacturer, consist of a rotating wheel cage (with the number of revolutions/day recorded by a cyclometer attached to the wheel axis) plus an adjoining feed cage.…”
Section: Exercise Training Insulin Resistance • Hyperinsulinemiamentioning
confidence: 99%
“…In this context, we have previously demonstrated that insulin-stimulated glucose uptake is enhanced in exercise-trained rats 8 and that the hyperinsulinemia associated with feeding rats a high fructose diet is attenuated if rats are allowed to run spontaneously.…”
mentioning
confidence: 99%